Improving Students’ Learning Outcomes in Indonesian Language Subject on Writing Texts of Fantasy Materials Through the Application of Problem Based Learning Learning Models - Irman Irman (Journal of Teaching and Education, 2023)
One of the causes of low learning outcomes in low student Indonesian lessons is the application of learning models that are less able to make students active in participating in learning activities. So it is necessary to innovate learning models that can activate students. The purpose of this study is to analyze the application of the Problem Based Learning learning model to the results of learning Indonesian, especially the lesson of writing students' fantasy story texts. This research is a type of classroom action research with 2 cycles. With research subjects namely class VIII students totaling 32 students. data is collected by giving a test of learning outcomes to students. The collected data were analyzed using quantitative descriptive statistical analysis techniques. The results of the study in the first cycle showed an average value of 77, while in the second cycle, it was 82. So it can be concluded that the use of the Problem Based Learning learning model can improve student learning outcomes. The implication of this research is to teach students to work together in groups, use information to try to solve problems and students are trained to synthesize knowledge and skills before they apply them to problems.